2015
DOI: 10.1177/0954406215570385
|View full text |Cite
|
Sign up to set email alerts
|

A new accuracy design for a 6-dof docking mechanism

Abstract: The accuracy design is an effective approach in accuracy improvement for 6-dof docking mechanism, which involves accuracy analysis and synthesis. To improve the efficiency for accuracy analysis, the number-theoretic method (NTM)-based simulation with Sobol point set is investigated. Compared with traditional Monte Carlo (MC) simulation, Sobol set-based NTM can attain the same precision with only 1/10 sampling size of MC simulation. The accuracy synthesis process considers process ability and adopts orthogonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Taguchi-like methods have been proposed with different experimental designs to take into account kinematic and dynamic parameters [101,102], joint clearances and additional errors from assembly and operating conditions [103], and sets of poses of the mechanism with reduction to a single performance index [104]. Both experimental and optimization methods have been attempted for specific types of mechanisms such as robotic manipulators [105,106]. A related problem has also been addressed for machine tools through the statistical analysis of multibody models [107].…”
Section: Tolerance Allocation On Linkagesmentioning
confidence: 99%
“…Taguchi-like methods have been proposed with different experimental designs to take into account kinematic and dynamic parameters [101,102], joint clearances and additional errors from assembly and operating conditions [103], and sets of poses of the mechanism with reduction to a single performance index [104]. Both experimental and optimization methods have been attempted for specific types of mechanisms such as robotic manipulators [105,106]. A related problem has also been addressed for machine tools through the statistical analysis of multibody models [107].…”
Section: Tolerance Allocation On Linkagesmentioning
confidence: 99%
“…Insight on parameter variances of this mechanism was provided with the sensitive maps, and the efficiency and practicality were demonstrated with the proposed method. Li et al (2015) investigated the tolerance design problem of a 6-DOF space docking mechanism using uniform design, and concerned the efficiency and precision of MC simulation in DOE. The tolerance of the component in the mechanism was properly broadened without any loss of output accuracy, and the manufacturing cost was reduced to a certain extent.…”
Section: Mechanism Tolerance Synthesis Reviewmentioning
confidence: 99%
“…We have found that as the dimension of a problem increases, the priorities in analytical precision and efficiency based on NTM are more significant over traditional Monte Carlo simulation. This simulation belongs to a 12-dimension problem, and Li et al had applied Sobol-set based MC in tackling accuracy analysis problem of a six-dof docking mechanism with 42 dimensions (Li et al, 2015). as the dimension increases, the pseudo-random cannot guaranty the investigated space where the high-dimension points uniformly are scatted.…”
Section: Effectiveness Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Pose accuracy of 6-degrees of freedom (dof) docking mechanism as one of the critical indexes in assembly quality control process does not only demand a higher dimensional precision of components but also requires a higher success rate for assembly work. 1,2 To lower the pose errors and improve success rate of the mechanism assembled, the prediction on assembly performance is essential before assembly process is implemented in workshop. The recently developed virtual manufacturing technology provides an effective support for this work.…”
Section: Introductionmentioning
confidence: 99%